Star tales - Ridpath, Ian (The Lutterworth Press, 2018)
"Every night, a pageant of Greek mythology circles overhead. Perseus flies to the rescue of Andromeda, Orion faces the charge of the snorting Bull, and the ship of the Argonauts sails in search of the Golden Fleece. Constellations are the invention of the human imagination, not of nature. They are an expression of the human desire to impress its own order upon the apparent chaos of the night sky. Modern science tells us that these twinkling points of light are glowing balls of gas, but the ancient Greeks, to whom we owe many of our constellations, knew nothing of this. Ian Ridpath, well-known astronomy writer and broadcaster, has been intrigued by the myths of the stars for many years. Star Tales is the first modern guide to combine all the fascinating myths in one book, illustrated with the beautiful and evocative engravings from two of the leading star atlases: Johann Bode's Uranographia of 1801 and John Flamsteed's Atlas Ceolestis of 1729. This is an excellent reference and the perfect gift for the armchair astronomer and those interested in classical mythology alike"--Publisher